Antioxidant, Antidiabetic and Anticancer Effects of Persimmon Leave Extracts In vitro - Doaa, F. Hassan; Hossam, M. Abotaleb (Food Technology Research Journal)
This study aims evaluate the antioxidant, antidiabetic and anticancer effects of persimmon leave extracts (PLEs). The results showed that all extracts had high amounts of phenolic and flavonoids components, the aqueous hot and cold extract exhibited the highest antioxidant activity determined by two methods (DPPH, ABTS), Vit. C and free sugar fractions determined by HPLC than ethanolic ex. Also, these extracts (aqueous hot and old) had high inhibition % of α- glucosidase and α- amylase enzymes that effect on diabetes and anticancer effect on two type of cancer cell the first was: CaCo2 cell of colon and the hot ex have the highest inhibition % than other extracts, and the second was 549 cells of homo sapiens epithial adherent cancer cell and cold extract was the highest inhibition % against it. In this study we concluded that all aqueous extracts had higher effect as antioxidant, antidiabetic and anticancer than ethanolic.